Closed-form solutions for FRP strengthening of masonry vaults. (15th January 2015) - Baratta, Alessandro; Corbi, Ottavia
Abstract: In the paper one focuses on masonry vaults and on the proper positioning of composite reinforcements for reducing the lateral thrust, on the basis of a theoretical formulation which is founded on a equilibrium approach devoted at selecting shapes of load patterns that can be equilibrated by relevant admissible solutions, also accounting for so called non-manageable loads. Areas to be strengthened are identified and the practically immediate and operative applicability of the procedure is shown through implementation in ad hoc set up calculus codes.